Association between recorded medication reviews in primary care and adequate drug treatment management - a cross-sectional study - Naldy Parodi López; Staffan A. Svensson; Susanna M. Wallerstedt (Taylor & Francis Group, 2021)
Objective To investigate the association between a recorded procedure code for a medication review and adequate drug treatment management, and to explore factors associated with this code. Design and setting Cross-sectional study; two primary health care centres, in Region Västra Götaland, Sweden. Subjects A total of 302 consecutive patients (≥65 years old, 59% female; median number of drugs: six) requiring a non-urgent consultation with a physician in October-November 2017. Main outcome measure Adequate drug treatment management (treatment that did not require any further action), determined in consensus by two specialists in family medicine blinded to the medication review code. Results Adequate drug treatment management was, overall, less common in those with a recorded medication review over the last year: 63% versus 73% (p = 0.047). This negative association was evident among patients aged 65-74 years: 49% versus 74% (p = 0.003), but absent in those ≥75 years old: 67% versus 70% (p = 0.77). Recommendations from consensus included the search for additional information to be able to make a decision regarding initiation or withdrawal of a drug (n = 53), withdrawal of a drug (n = 41), or ordering a laboratory test (n = 25). Factors associated with a recorded procedure code included age above the remuneration limit of 75 years (odds ratio: 9.8; 95% confidence interval 5.0-19), type 2 diabetes (3.0 (1.5-6.2)), hypertension (2.4 (1.2-4.8)), and depression (2.5 (1.02-6.0)). Conclusions The presence of a recorded medication review was not positively associated with adequate drug treatment management but was associated with the age limit for remuneration, and some chronic diseases.Key points To improve drug treatment in older people in primary care, a remuneration system linked to recorded medication reviews has been introduced. In this study, fewer patients with than without a recorded medication review (63% versus 73%) had adequate drug treatment management. A recorded medication review was ten times more common in those ≥75 years, that is, the age limit for remuneration. Recorded codes for medication reviews were also common in those with type 2 diabetes, hypertension, and depression.